Simultaneous Determination of Three Active Ingredients in Wubishan Capsule by HPLC - Du, Zhen; Fan, Chenling (Asian Journal of Chemistry, 2014)
To establish an HPLC method for the simultaneous determination of 3 bioactive ingredients in Wubishan capsule. HPLC conditions included Kromasil-C18 column (250 mm × 4.6 mm, 5 μm) and the mobile phase was a mixture of MeOH-CH3CN-H2O (13:6:81). The flow rate was 1.0 mL/min, the column temperature was at 30 °C and the UV detection wavelength was 254 nm. The 3 active ingredients had good linear relationships: guanosine in the range of 0.0915-4.575 μg (R2 = 0.999 3), loganin in the range of 0.116-5.801 μg (R2 = 0.999 0) and schizandrin in the range of 0.0398-1.990 μg (R2 = 0.999 3). Their average recoveries were 99.1 % (RSD = 1 %), 98.7 % (RSD = 2.4 %) and 97.1 % (RSD = 1.0 %), respectively. This method was steady with high precision and good repeatability and could be used for the determination of the 3 active ingredients and quality control of Wubishan capsule.